Registos geomorfológicos e sedimentares do Plio-Plistocénico de Peniche - Atouguia da Baleia - Cunha, Pedro P. (2017)
A characterization and interpretation of the Pliocene and Pleistocene geomorphological and sedimentary records of Peniche - Atouguia da Baleia littoral are here presented. Several wave-cut platforms were characterized and mapped, respectively, at: 33-36 m, a vast culminant surface only locally preserved, associated with yellowish fine to very coarse pebbly sands, and also by very coarse whitish sands; 24-27 m, a very wide wave-cut platform covered by whitish bioclastic pebbly sands sometimes cemented; 20-21 m, only locally represented, with some very coarse whitish very coarse sandstones; 15-17 m, covered by fine to very coarse pebbly yellowish sands, with a fossiliferous travertine breccia at top; 10-12 m, with yellowish very coarse sandstones, with a travertine breccia at top; and 6-8 m, with a marine conglomerate and an upper coarse sandstone. The culminant marine platform and associated marine deposits are correlated with the important marine incursion dated as 3.7 Ma and the five marine terraces that are located above the modern wave-cut platform ate correlated to the periods of highest sea-level during the Pleistocene MISs. In Furninha cave, the succession of aeolian fine sands intercalated with levels rich in fossils containing industries of Middle to Upper Palaeolithic should bracket the interval 80-12ka (MIS4, MIS3 and MIS2), coeval with the lowering of sea-level and cold climate conditions. The consolidated late Pleistocene aeolian pink fine sands are covered by whitish loose fine sands (MIS1).